2020
DOI: 10.1186/s12944-020-01390-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism gene-wide profile and survival signature of lung adenocarcinoma

Abstract: Background Lung cancer has high morbidity and mortality across the globe, and lung adenocarcinoma (LUAD) is the most common histologic subtype. Disordered lipid metabolism is related to the development of cancer. Analysis of lipid-related transcriptome helps shed light on the diagnosis and prognostic biomarkers of LUAD. Methods In this study, expression analysis of 1045 lipid metabolism-related genes was performed between LUAD tumors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Altered gene expression is closely related to cancer metabolism including lipid metabolism [53]. There was a report that glycerophospholipid metabolism, fatty acid metabolism, and eicosanoid signaling were significantly enriched in lung adenocarcinoma compared to normal tissue [54]. In addition, the MYC gene has been known as an oncogene that promotes cancer cell growth and proliferation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Altered gene expression is closely related to cancer metabolism including lipid metabolism [53]. There was a report that glycerophospholipid metabolism, fatty acid metabolism, and eicosanoid signaling were significantly enriched in lung adenocarcinoma compared to normal tissue [54]. In addition, the MYC gene has been known as an oncogene that promotes cancer cell growth and proliferation [55].…”
Section: Discussionmentioning
confidence: 99%
“…Hilvo et al (2011) demonstrated that the lipids in the breast cancer tissue were correlated with tumor progression and patient survival. Moreover, previous studies have demonstrated that lipid metabolism related genes (LMRGs) had potent prognostic potential in multiple types of tumors, including ovarian carcinomas (Zheng et al, 2020), lung adenocarcinoma (LAUD) (Li et al, 2020), pancreatic cancer (Ye et al, 2021), hepatocellular carcinoma (HCC) (Hu et al, 2020), renal cell carcinoma (RCC) (Bao et al, 2019) and diffuse gliomas (Wu et al, 2019). As such, targeting lipid metabolism has been regarded as a novel therapeutic strategy for tumor treatment (Visweswaran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence also indicates that aberrant lipid metabolism is involved in drug resistance during cancer treatment ( Iwamoto et al, 2018 ; Cao, 2019 ). Previous studies have reported that risk signatures derived from lipid metabolism-associated genes (LMAGs) exhibit potent capability in predicting the prognosis of various tumors, including serous ovarian carcinomas ( Zheng et al, 2020 ), clear cell renal cell carcinomas ( Zheng et al, 2020 ), pancreatic cancer ( Ye et al, 2021 ), lung adenocarcinomas ( Li et al, 2020 ), and diffuse gliomas ( Li et al, 2020 ). However, the prognostic value of LMAGs in patients with BRCA remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%